1993
DOI: 10.1103/physrevlett.71.1027
|View full text |Cite
|
Sign up to set email alerts
|

Singular dynamical renormalization group and biased diffusion on fractals

Abstract: An exact renormalization group describes extremely slow, logarithmic diffusion in the presence of a biasing field on ramified fractal structures. Recursion equations are singular at the fixed point and the standard analysis to extract asymptotic behaviors has to be reconsidered. The model reproduces mechanisms working for biased diffusion on percolation clusters. For 1 ~d structures, logarithmic diffusions generalizing that discussed by Sinai [Theory Probab. Its Appl. 27, 256 (1982)] are obtained by the same m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 16 publications
4
39
0
Order By: Relevance
“…¿From a mathematical point of view this corresponds to the possibility of eliminating by substitution a set of equations from system (85) or (87) obtaining a system which is similar to the initial one after a suitable redefinition of the coupling parameters. Examples of exactly decimable fractals are the Sierpinski Gasket (Fig.3), [25,26,27,28], the T −fractal, shown in Fig.4 [29,30], the branched Koch curves, in Fig.5 [31]. In general, all deterministic finitely-ramified fractals are exactly decimable.…”
Section: Renormalization Techniquesmentioning
confidence: 99%
“…¿From a mathematical point of view this corresponds to the possibility of eliminating by substitution a set of equations from system (85) or (87) obtaining a system which is similar to the initial one after a suitable redefinition of the coupling parameters. Examples of exactly decimable fractals are the Sierpinski Gasket (Fig.3), [25,26,27,28], the T −fractal, shown in Fig.4 [29,30], the branched Koch curves, in Fig.5 [31]. In general, all deterministic finitely-ramified fractals are exactly decimable.…”
Section: Renormalization Techniquesmentioning
confidence: 99%
“…In the near past a considerable research activity has been devoted to the studies of recursion relations which have a singular structure near the pertinent fixed points [1][2][3][4][5][6]. It was found that, under certain conditions, these singularities can lead to an unusual critical behavior of relevant physical quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The fixed point equations are singular and exhibit a boundary layer [17]. It provides a tangible case of a singularity in the RG [10,18] that is easily interpreted in terms of the physics.…”
mentioning
confidence: 99%
“…Much attention has thus been paid to model subdiffusion on designed structures with some of the trappings of disordered materials, exemplified by Refs. [6][7][8][9][10][11]. Even self-organized critical processes can be shown to evolve sub-diffusively, controlled by the memory of all past events [12].…”
mentioning
confidence: 99%